2024
DOI: 10.1007/s12311-024-01700-2
|View full text |Cite
|
Sign up to set email alerts
|

Content Validity of the Modified Functional Scale for the Assessment and Rating of Ataxia (f-SARA) Instrument in Spinocerebellar Ataxia

Michele Potashman,
Katja Rudell,
Ivanna Pavisic
et al.

Abstract: The functional Scale for the Assessment and Rating of Ataxia (f-SARA) assesses Gait, Stance, Sitting, and Speech. It was developed as a potentially clinically meaningful measure of spinocerebellar ataxia (SCA) progression for clinical trial use. Here, we evaluated content validity of the f-SARA. Qualitative interviews were conducted among individuals with SCA1 (n = 1) and SCA3 (n = 6) and healthcare professionals (HCPs) with SCA expertise (USA, n = 5; Europe, n = 3). Interviews evaluated symptoms and signs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Through collection of qualitative data from semi-structured interviews, carried out in conjunction with this quantitative study, it was identified that the clinical relevance of the f-SARA could be improved with the inclusion of manual dexterity items such as the finger-nose and finger chase [47]. However, this would be a reversion to the original SARA scale and does not incorporate insights from the analysis of US natural history data and the troriluzole phase 2 study, which suggested appendicular items are less sensitive to change and/or are more variable over 1 year [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Through collection of qualitative data from semi-structured interviews, carried out in conjunction with this quantitative study, it was identified that the clinical relevance of the f-SARA could be improved with the inclusion of manual dexterity items such as the finger-nose and finger chase [47]. However, this would be a reversion to the original SARA scale and does not incorporate insights from the analysis of US natural history data and the troriluzole phase 2 study, which suggested appendicular items are less sensitive to change and/or are more variable over 1 year [20,21].…”
Section: Discussionmentioning
confidence: 99%